Quality Assessment of Silver Arabic Chicken Eggs with the Addition of Chitosan in Rations - Eli Sahara; S Sandi; F Yosi; R Nanda (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
The quality of chicken eggs is greatly influenced by the nutrient ration consumed. Egg quality can be observed from the external and internal eggs. The ration directly affects the external and internal quality of the eggs. The research objective was to analyze the effect of chitosan addition in the ration on the internal quality of chicken eggs. The study used a completely randomized design (CRD) with 6 treatments and 5 replications, each replication consisting of 2 Silver Arabic Chickens aged 4.5 months. The study was conducted for 7 weeks. The treatments given were: R0 (control ration without chitosan), R1 (ration + chitosan 0.5%), R2 (ration + chitosan 1%), R3 (ration + chitosan 1.5%), R4 (ration + chitosan 2%), R5 (ration + chitosan 2.5%). The parameters were measured in haugh units, albumen index, albumen and yolk weight. The results demonstrate that the addition of chitosan in the ration showed the same results (P > 0.05) on the haugh unit value, albumen index, albumen and yolk weight. The conclusion of this study indicates that the provision of chitosan in the ration has not had an effect on the internal quality of the Silver Arabic Chickens eggs.